Advancing Post-Structural Institutionalism: Discourses, Subjects, Power Asymmetries, and Institutional Change. Issue 3 (2nd October 2018) - Larsson, Oscar
ABSTRACT: Colin Hay's and Vivien Schmidt's responses to my previous critical engagement with their respective versions of neo-institutionalism raise the issue of how scholars may account for the ideational power of political processes and how ideas may generate both stability and change. Even though Hay, Schmidt, and I share a common philosophical ground in many respects, we nevertheless diverge in our views about how to account for ideational power and for actors' ability to navigate a social reality that is saturated with structures and meaning. There continues to be a need for an analytical framework that incorporates discourse and a constitutive logic based upon the power in ideas. Post-structural institutionalism (PSI) analyzes discourse as knowledge claims by means of the concept of a constitutive causality, analytically identified in respect to institutions, such that the substantive content of ideas/discourse provides ideational power and generates immanent change.